THE ROLE OF PRE-15TH CENTURY PRINTING TECHNIQUES, THE RENAISSANCE PERIOD, AND THE INDUSTRIAL REVOLUTION AT THE END OF THE 18 TH CENTURY - Priatna, Angga (P3M Politeknik Negeri Media Kreatif, 2024)
The purpose of this article is to provide the public with an understanding of the important role of printing techniques in the past time. The methodology used by author is based on literature studies, The results of this research reveal, books and posters are two secondary communication media that record printing techniques at important times in history of the world, namely when the European continent experienced what is called a rebirth or renaissance, and the starting point for the birth of the Industrial Revolution which has continued to this day. The author found that during the excavation of ancient knowledge, printing techniques contributed to the dissemination of various ancient literature which was redesigned with text arrangements and graphic elements in the form of literacy which was read by the public, studied, and ultimately was able to rebuild a more modern and modern civilization collective. Even during the Industrial Revolution, printing techniques were used on posters to disseminate commercial and informational messages. Thus, the author concludes that printing techniques are important not only in disseminating knowledge and creating art work as the the books and posters, but also as an interesting historical study for the wider public to understandKeywords: Printing techniques, books and posters, renaissance and industrial revolution